Validated High Performance Thin Layer Chromatography Method for Simultaneous Estimation for Gallic Acid and Quercetin in Polyherbal Blend and Their Quantitative Estimation - Gandhi, S.P.; Gawhane, A.R.; Kapse, S.D.; Nagore, D.; Chitlange, S.S. (Karagandy University of the name of academician E.A. Buketov, 2022)
Simple, sensitive high performance thin layer chromatography method for the estimation of gallic acid and quercetin in in-house polyherbal blend has been developed and validated. Methanolic solution of herbal blend comprising of Emblica officinalis, Camellia sinensis and Garcinia cambogia was used for analysis. The separation was performed on TLC aluminum plates precoated with silica gel G60 F254 and toluene: ethyl acetate: formic acid (5:1.5:1 v/v/v) at 254 nm scanning wavelength. The system gave well resolved peaks for gallic acid and quercetin at Rf 0.14 and Rf 0.29 respectively. The method validated as per ICH Q2R1 guidelines which shows regression co-efficient 0.9939 for gallic acid and 0.9988 for quercetin in range of 2–6 μg/ml. Recovery of gallic acid and quercetin was found in range of 98–102 % which confirms the accuracy of method. Precision study (interday & intraday) showed that the relative standard deviation is less than 2 %, showing method is well precise. Proposed validated HPTLC method is simple, precise, specific, robust and accurate, and could find application in routine quality-control analysis. The method was used for quantitative estimation of gallic acid and quercetin in the polyherbal blend and was found as 1.648 % w/w and 3.165 % w/w respectively.
Көпшөпті қоспадағы галл қышқылы мен кверцетинді бір уақытта бағалау және сандық анықтау үшін расталған жоғарыөнімді жұқа валидацияланған хроматография әдісі
Валидированный метод высокоэффективной тонкослойной хроматографии для одновременной оценки содержания галловой кислоты и кверцетина в политравной смеси и их количественная оценка
Keywords: gallic acid; quercetin; simultaneous estimation; high performance thin layer chromatography; validation; quantification; polyherbal; herbal; extracts